Study of correlation between symptoms and signs in women with anterior vaginal wall prolapse - Bijwe, Smita Anand; Rajbhara, Pooja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pelvic organ prolapse is a common, distressing and disabling condition affecting up to 30% of the women, 20- 60 years of age, attending Gynaecology outpatient clinics. Objective of present work was to know the effect of Pelvic Organ Prolapse (POP) on micturition symptoms. Methods: Descriptive study including 64 women presenting with POP symptoms. Subjects were evaluated using POP-Quantification system, Urinary Distress Inventory. Results: Women were asked to rate the extent to which they were bothered by their urinary function on a scale of 1 to 10, with 1 being not at all and 10 being extremely. Ten women (16%) reported 1 to 4, 23 (37%) reported 5 to 7, and 29 (47%) reported and gt;8. Conclusions: Strong association does exist between POP and micturition symptoms which are obstructive in nature and those causing urge incontinence.